Metabolism of carbohydrate-containing biopolymers in liver and gastric mucosa of rats with experimental diabetes and varying stress resistance - Svetlana Vladimirovna Protasova (Endocrinology Research Centre, 2010)
Aim. To measure concentration of carbohydrate-containing biopolymers in liver and gastric mucosa of rats with alloxan diabetes and varying stressresistance. Materials and methods. The ?open field? test was used to allocate the animals to 2 groups (stress-sensitive and stress-resistant). Insulin-dependentdiabetes was induced by a single s/c injection of alloxan tetrahydrate (170 mg/kg). Total glycosaminoglycanes and gyaluronidase activity were measuredin gastric mucosa. Results. Concentration of glycosaminoglycanes (sialic acids) in the liver increased in animals of both groups and reached a maximum on day 30. Conclusion. Metabolism of sialoglycoproteins in gastric mucosa was dominated by catabolic processes most intense on day 45 after induction of experimentaldiabetes